Virtual School Counselling and Covid-19 as Seen Through an Organizational Learning Lens - Hornor, Tara; Westberry, Lee A. (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2023)
This article examines the shift to virtual school counselling through an organizational learning framework developed by Mary Crossan. This framework links the individual, group, and organization levels of an institution through the social and psychological processes of organizational learning, including intuiting, interpreting, integrating, and institutionalizing. The findings highlight four major challenges of virtual learning—technology, work-life balance, legal ramifications, and virtual counselling skills and abilities—that were partially or fully overcome with solutions that became institutionalized.